A System for Computer-Aided Gating Design for Single and Multi-Cavity Injection Moulds - Kumar, Vijay; Virdi, Roshan Lal (Asian Journal of Engineering and Applied Technology, 2014)
Design of injection moulding dies (called moulds) is a time consuming and complex activity that requires domain knowledge and vast experience of the die-designer besides information about manufacturing resources, part geometry, number of cavities, etc. The gating design is of great importance for reducing lead time and cost of part produced and to achieve first-piece-right. The gating design encompasses several steps, involves complex computational work, and requires a number of iterations. In the present research work an attempt has been made to develop a computer-aided system, which facilitates gating design of an injection mould taking part CAD file as input. The gating parameters are calculated by taking part geometry, material and number of cavities as input. The proposed system is divided into three modules, namely Gate design, Runner design and Sprue design. To demonstrate the capabilities of proposed system, it was tried for a number of parts and the results for two industrial case study parts are presented. Proposed system is a step forward to design-manufacturing integration for injection moulding process.